2014
DOI: 10.1136/amiajnl-2013-001993
|View full text |Cite
|
Sign up to set email alerts
|

Development and use of active clinical decision support for preemptive pharmacogenomics

Abstract: BackgroundActive clinical decision support (CDS) delivered through an electronic health record (EHR) facilitates gene-based drug prescribing and other applications of genomics to patient care.ObjectiveWe describe the development, implementation, and evaluation of active CDS for multiple pharmacogenetic test results reported preemptively.Materials and methodsClinical pharmacogenetic test results accompanied by clinical interpretations are placed into the patient's EHR, typically before a relevant drug is prescr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
180
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 187 publications
(182 citation statements)
references
References 38 publications
0
180
1
1
Order By: Relevance
“…63 This model has been effective for pharmacogenomics. 64 Finally, medical decision support systems must continue to be designed-current applications in progress relate to pharmacogenomics 56 -so that health professionals can access up-to-the-minute relevant information and respond appropriately to the concerns they hear when interacting with their patients. 57 With the advancement of genetic technologies and continued workforce shortages of geneticists and genetic counselors, 58 PCPs will need to assume a greater responsibility in genetics medicine related to the anticipatory guidance and disease prevention that lie within their purview.…”
Section: Discussionmentioning
confidence: 99%
“…63 This model has been effective for pharmacogenomics. 64 Finally, medical decision support systems must continue to be designed-current applications in progress relate to pharmacogenomics 56 -so that health professionals can access up-to-the-minute relevant information and respond appropriately to the concerns they hear when interacting with their patients. 57 With the advancement of genetic technologies and continued workforce shortages of geneticists and genetic counselors, 58 PCPs will need to assume a greater responsibility in genetics medicine related to the anticipatory guidance and disease prevention that lie within their purview.…”
Section: Discussionmentioning
confidence: 99%
“…41 Pretest (pregenotype) alerts are presented when a prescriber orders codeine for a patient for whom there is no CYP2D6 test result in the EHR (Fig 4A). This alert communicates that a CYP2D6 genotype should be obtained before prescribing codeine, and a CYP2D6 test may be ordered directly from the alert screen.…”
Section: Pharmacogenetics-based Strategy For Codeine Prescribingmentioning
confidence: 99%
“…(Fig 2) and clinical decision support (CDS) alerts that are presented via the EHR. 40,41 For those patients who do not have a CYP2D6 result available through PG4KDS, a single gene test for CYP2D6 may be ordered as a routine clinical laboratory test to guide codeine prescribing, an option that has a turn-around time of ∼5 to 7 days. 42 St. Jude hematologists often order a CYP2D6 genotype before codeine is prescribed, anticipating the future use of codeine as a potential therapeutic option for patients with SCD.…”
mentioning
confidence: 99%
“…In personalized and precision medicine, provider knowledge and decision support have been identified as key issues to the integration of new genetic and genomic applications [20]. While some groups are developing EMR-based PGx CDS alerts [21,22] PGx consultation service staffed by a pharmacist and a physician geneticist [23]. Previous studies have demonstrated that pharmacists are well suited to provide support, able to create effective relationships with providers and achieve high provider acceptance of pharmacist recommendations [24,25].…”
mentioning
confidence: 99%